Animal thematic postage stamps: State narratives from the colonial to the postcolonial / Kay Shin Yan - Kay , Shin Yan (2019)
This research exemplifies the postage stamps as part of the visual culture that facilitates the State narratives. It explores visual representations of animal thematic postage stamps that has so far been issued in North Borneo, Sarawak, British Malaya and Malaysia. Since animal thematic stamps were introduced in the colonial era and persisted into the postcolonial era, this research aims to record and analyse the change of visual representations in both main subject matter (animals) and periphery of the subjects (decorative art and languages). It demonstrates how decorative elements evolved across eras as well as how the animals being represented in official disseminations, which consequently reflect that the ways of seeing animals are culturally or socio-politically specific. More than hundreds of animal thematic stamps that has so far been issued in Malaysia, included different definitives, commemorative stamps or special issues have been examined ranged from years 1867 to 1991. In order to get a bigger picture on the visual changes, the researcher looked and compared the animal stamps between different nations, as well as studied the different thematic stamps issued within the nation. Besides that, all animal thematic stamps of Malaysia that issued before 1992 are rearranged in different categories to understand the selection tendency of subject matters. Following that, this research is conducted in 2 phases. First phase is the data collection / background studies via digitalised databases as well as museum, archive centre and library visits. Second is the theoretical analysis and visual methodologies. This research reflects the visions of the Federal governments in different eras and reveals how the visual culture contributes to the formation of colonial or national identities.